2005
DOI: 10.1158/1078-0432.ccr-04-2509
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Gene Expression in Different Histotypes of Epithelial Ovarian Cancer Correlate with Those in Normal Fallopian Tube, Endometrium, and Colon

Abstract: Purpose: Epithelial ovarian cancers are thought to arise from flattened epithelial cells that cover the ovarian surface or that line inclusion cysts. During malignant transformation, different histotypes arise that resemble epithelial cells from normal fallopian tube, endometrium, and intestine. This study compares gene expression in serous, endometrioid, clear cell, and mucinous ovarian cancers with that in the normal tissues that they resemble. Experimental Design: Expression of 63,000 probe sets was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
207
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 282 publications
(226 citation statements)
references
References 50 publications
13
207
0
6
Order By: Relevance
“…Advances in molecular characterization of histological types has allowed for development of targeted molecular therapies based on the specific subtype (Perou et al, 2000;van 't Veer et al, 2002). To reveal the molecular background of OCCC, several microarray studies identified genes that are specifically expressed in OCCC (Schwartz et al, 2002;Schaner et al, 2003;Tsuchiya et al, 2003;Marquez et al, 2005;Zorn et al, 2005). However, in each case only the respective original microarray data set was analyzed, and thus these reports did not test for reproducibility of the OCCC gene expression profiles that each defined.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Advances in molecular characterization of histological types has allowed for development of targeted molecular therapies based on the specific subtype (Perou et al, 2000;van 't Veer et al, 2002). To reveal the molecular background of OCCC, several microarray studies identified genes that are specifically expressed in OCCC (Schwartz et al, 2002;Schaner et al, 2003;Tsuchiya et al, 2003;Marquez et al, 2005;Zorn et al, 2005). However, in each case only the respective original microarray data set was analyzed, and thus these reports did not test for reproducibility of the OCCC gene expression profiles that each defined.…”
Section: Resultsmentioning
confidence: 99%
“…These 437 overlapping probe sets clearly detect OCCC-specific tumor clusters using hierarchical clustering within GSE6008 (d) and KyotoOv38 (e). In the analysis of the PMID16144910 data set (Marquez et al, 2005), a tumor cluster containing six OCCC tumors was clearly detected using the OCCC signature (overlapping OCCC probe set) (f, left), whereas the nonoverlapping probe sets from GSE6008 (f, middle) and from KyotoOv38 (f, right) did not generate such a defined OCCC tumor cluster. For GSE2109, the overlapping OCCC signature generated gene clusters enriched for OCCC tumors (g, left), whereas the nonoverlapping probe sets did not detect an OCCC-specific tumor cluster (g, middle and right).…”
Section: Gse6008mentioning
confidence: 99%
See 2 more Smart Citations
“…8,10,16 However, it is known that in addition to loss of TP53 function, numerous other disturbances in gene expression characterize high-grade serous cancers, and it is logical to presume that precursors contain some of these functional alterations. 17,18 One of these genes, PAX2, has been shown to be down-regulated in both high-grade mü llerian (endometrioid or serous) pelvic carcinomas and in benign and neoplastic endometrium. 16,[19][20][21] Recently, we identified a second form of SCOUT in the oviduct that exhibited normal TP53 genotype but on further analysis, frequently showed a loss or reduction of PAX2 immunostaining.…”
Section: Discussionmentioning
confidence: 99%